Near-infrared Polarimetry and Interstellar Magnetic Fields in the Galactic Center. (5th March 2015) - Nishiyama, S.; Hatano, H.; Nagata, T.; Tamura, M.
Abstract: We present a large-scale view of the magnetic field (MF) in the central 3° × 2° region of our Galaxy. There is a smooth transition of the large-scale MF configuration in this region.